Abrasion resistant member and manufacturing method of abrasion resistant member
Patent Information
- Application Number
- JP2023129751
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025186000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a wear-resistant member having a coating layer made of an alloy material having excellent wear resistance formed on a metal substrate, and to a method for manufacturing the wear-resistant member. [Background technology]
[0002] Patent Document 1 describes an example of a highly tough hardfacing material with excellent wear resistance, corrosion resistance, and powder build-up weldability, which contains 30.0 to 48.0 weight % Ni, 1.5 to 15.0 weight % W and / or 1.0 to 6.5 weight % Mo, with the total of W and Mo being a maximum of 15.0 weight % or less, and optionally containing one or more of Fe, Co, C, B, Al, Si, Nb, and Ti, and in the case of a powder used for powder build-up welding, optionally containing 0.01 to 0.12 weight % of one or more of Al, Y, misch metal, Ti, Zr, and Hf, and optionally containing 0.01 to 0.1 weight % of oxygen, with the balance being 40 weight % or more of Cr. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 5-271841 Summary of the Invention [Problem to be solved by the invention]
[0004] Valves play an important role in controlling the direction and amount of fluid flow, and because they are used in large quantities, they have a strong influence on maintenance cycles. Therefore, the wear resistance of valves is one of the important properties that affect the lifespan of the components.
[0005] For example, the simplest method for improving the wear resistance of valve components that constitute a valve, such as a valve body and a valve seat, is to form the entire component from a material with excellent wear resistance. However, such a simple method is not necessarily the optimal solution from the viewpoint of other properties required for the component, such as mechanical strength, toughness, cost, etc.
[0006] On the other hand, there is a method of forming a valve member by using a conventional material that is excellent in mechanical strength, toughness, and cost as a base material and forming a coating layer of a material with excellent wear resistance on the valve disc surface and the valve seat surface (see, for example, Patent Document 1). Co-based alloy materials such as Stellite (registered trademark) and TRIBALOY (registered trademark) have been widely used as materials for such coating layers.
[0007] However, these Co-based alloys pose a risk of radiation exposure to workers during inspection due to the release of activated Co.
[0008] For example, Co-based alloys are surface-hardened alloys that extend the life of sliding parts, such as valve components and control rod drive mechanism components used in nuclear power plants. However, Co dissolved by friction or corrosion turns into the radioactive isotope Co60 in the reactor core, and when Co60 undergoes beta decay in steam piping, it emits gamma rays. Since this beta decay of Co60 is the main source of radiation exposure in nuclear power plants, there is a demand for the development of Co-free alloys.
[0009] Furthermore, Co alloys with excellent wear resistance have been used for valve components in nuclear power plants. However, as mentioned above, there is a risk of workers being exposed to radiation due to the dissolution of activated Co during inspection, and overlay welding involves melting the powder and base material at the same time to weld, which not only reduces corrosion resistance but also dilutes the powder components with the base material, so that during maintenance of the valve seat, it is necessary to scrape off the overlay by lapping to smooth the overlay surface, which increases the dilution rate.
[0010] The present invention provides a wear-resistant member and a method for manufacturing a wear-resistant member that can reduce the amount of radiation exposure of workers caused by Co elution compared to conventional methods. [Means for solving the problem]
[0011] The present invention includes a number of means for solving the above-mentioned problems. One example is a wear-resistant member comprising a substrate made of carbon steel and a coating layer made of a Cr-based alloy material formed on the surface side of the substrate, wherein the coating layer has a dilution ratio which is determined by the mixing rate of the substrate in the coating layer, which is determined from the component ratio of the coating layer to the substrate when the increase in the main component of the substrate in the coating layer relative to the material before the coating layer is calculated, and the dilution ratio has a gradient in the range of 95% or less from the substrate side to the surface of the coating layer, and the outermost surface of the coating layer has a dilution ratio of 20% or less. Effect of the Invention
[0012] According to the present invention, it is possible to reduce the amount of radiation exposure of workers caused by elution of Co, as compared with the conventional art. Problems, configurations and effects other than those described above will become apparent from the following description of the embodiments. [Brief description of the drawings]
[0013] [Figure 1] 1A to 1C are process diagrams showing an example of a method for producing a wear-resistant member according to the present invention. [Diagram 2] 1 is a schematic diagram of a gate valve, which is an example of a wear-resistant member of the present invention. [Diagram 3] FIG. 3 is a partially enlarged view of FIG. [Figure 4] 4 is a schematic diagram of a globe valve as another example of the wear-resistant member of the present invention. FIG. [Diagram 5] FIG. 5 is a partially enlarged view of FIG. [Figure 6] 4 is a schematic diagram of a check valve as yet another example of the wear-resistant member of the present invention. FIG. [Figure 7] FIG. 7 is a partially enlarged view of FIG. [Figure 8] 1 is a photograph showing the appearance of the test specimen prepared. [Figure 9] 1 is a photograph showing the cross-section of a test specimen in an example. [Figure 10] FIG. 1 is a diagram showing an example of a dilution ratio of a test specimen in an example. [Figure 11] FIG. 1 is a diagram showing an example of a dilution ratio of a test specimen in an example. [Figure 12] FIG. 1 is a diagram showing an example of a dilution ratio of a test specimen in an example. [Figure 13] FIG. 1 is a diagram showing an example of hardness of a test specimen in an example. [Figure 14] FIG. 1 is a diagram showing an example of hardness of a test specimen in an example. [Figure 15] FIG. 1 is a diagram showing an example of hardness of a test specimen in an example. [Figure 16] FIG. 13 is a diagram showing an example of the relationship between the dilution ratio and hardness of a test specimen in an example. [Figure 17] FIG. 1 is a diagram showing an example of the relationship between the dilution ratio and hardness of a test specimen in an example. [Figure 18] FIG. 1 is a diagram showing an example of the relationship between the dilution ratio and hardness of a test specimen in an example. [Figure 19] 1 is a photograph of the appearance after a corrosion test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the embodiments of the wear-resistant member and the manufacturing method of the wear-resistant member of the present invention will be specifically described with reference to the drawings. However, the same symbols are used for the same states and steps, and duplicated explanations are omitted. Furthermore, the present invention is not limited to the embodiments described here, and can be appropriately combined with known technologies or improved based on known technologies within the scope of the technical idea of the invention. Furthermore, in the drawings used in this specification, the same or corresponding components are given the same or similar symbols, and repeated explanations of these components may be omitted.
[0015] In this specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower and upper limits. In the numerical ranges described in stages in the present invention, the upper or lower limit described in one numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in the present invention, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0016] In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.
[0017] The present inventors have investigated and examined the relationship between chemical composition, corrosion resistance, and Vickers hardness in Cr-based alloys, and have completed the present invention.
[0018] [Wear-resistant member and its manufacturing method] FIG. 1 is a process diagram showing an example of a method for producing a wear-resistant member according to the present invention.
[0019] As shown in FIG. 1, first, alloy powder 10 is used to form a build-up portion 22 made of a molten and solidified Cr-based alloy on the surface of a base material 21 made of carbon steel of a desired composition by an overlay welding process (step S1).
[0020] The substrate 21 is not particularly limited and may be made of various carbon steel-based compositions.
[0021] In the present invention, the build-up welding step S1 includes thermal spraying using metal powder.
[0022] There are no particular limitations on the overlay welding method, and conventional methods (e.g., shielded metal arc welding, CO2 welding, MAG (metal active gas) welding, MIG (metal inert gas) welding, TIG (tungsten inert gas) welding, submerged arc welding, PTA (plasma transferred arc) welding) can be used as appropriate.
[0023] The wear-resistant members 20, 20A are preferably sliding members or valve members, and in overlay welding of these sliding members or valve members, the overlay height is preferably 3 mm or more. In particular, in the sliding parts, the thickness is reduced by wear and further reworking is required to remove scratches during maintenance, so the overlay height is preferably 5 mm or more, and more preferably 6 mm or more.
[0024] The obtained wear-resistant member 20 may be used as it is as a component of various devices, but a further shaping process (step S2) may be carried out to adjust the dimensions and shape taking into account connection to other components, and the like, to process it into a wear-resistant member 20A having a coating portion 23.
[0025] The means for shaping the buildup portion 22 and processing it into the covering portion 23 includes, for example, cutting using a milling machine or grinding using a grindstone.
[0026] Here, in the cladding portion 22 made of a Cr-based alloy or the coating portion 23 obtained by machining the cladding portion 22, the alloy composition is diluted from the alloy powder 10 by the melting and diffusion of the components of the base material 21.
[0027] Since this dilution reduces the corrosion resistance and hardness of the buildup portion 22 or the coating portion 23, the dilution ratio determined by the mixing rate of the base material 21 in the buildup portion 22, which is determined from the component ratio of the buildup portion 22 to the base material 21 when determining the increase in the main component of the base material 21 in the buildup portion 22 relative to the alloy powder 10 before the formation of the buildup portion 22 in the wear-resistant member 20, has a gradient in the range of 95% or less from the base material 21 side to the surface of the buildup portion 22, and the dilution ratio at the outermost surface of the buildup portion 22 is 20% or less; alternatively, the dilution ratio determined by the mixing rate of the base material 21 in the coating portion 23, which is determined from the component ratio of the coating portion 23 to the base material 21 when determining the increase in the main component of the base material 21 in the coating portion 23 relative to the alloy powder 10 before the formation of the coating portion 23 in the wear-resistant member 20A, has a gradient in the range of 95% or less from the base material 21 side to the surface of the coating portion 23, and the dilution ratio at the outermost surface of the coating portion 23 is 20% or less.
[0028] Here, the dilution rate in the present invention is defined as "the increase in the main components of the base material in the buildup portion compared to the weld material before buildup is calculated, and the mixing rate of the base material in the buildup portion is calculated from the component ratio of the buildup portion and the base material."
[0029] In order to achieve the above-mentioned range of dilution ratio, the component ratio of the alloy composition of the alloy powder 10 used in the overlay welding process of step S1 is mainly adjusted. In this case, the welding conditions such as the heat input and welding speed in the overlay welding can be appropriately determined according to the composition. However, this is not limited to the adjustment of the composition of the alloy powder 10, and various adjustments can be made.
[0030] When higher corrosion resistance and higher hardness are required, the dilution ratio of the outermost surface of the cladding portion 22 or the covering portion 23 is preferably 16% or less, more preferably 6% or less, and most preferably 2% or less.
[0031] Moreover, it is desirable that the buildup portion 22 or the covering portion 23 has a region with a dilution rate of 16% or less that is 2 mm or more from the outermost surface. In this way, by making the dilution rate 16% or less in a region 2 mm or more from the outermost surface of the buildup portion 22 or the covering portion 23, it is possible to maintain a state in which the buildup portion 22 or the covering portion 23 is reliably formed and useful in consideration of actual operational conditions such as grinding allowance.
[0032] On the other hand, when the wear-resistant members 20, 20A are used as a valve, the buildup portion 22 or covering portion 23 near the substrate 21 has a higher dilution ratio, particularly in a multi-layer buildup process, toward the substrate 21. However, since the buildup portion 22 or covering portion 23 on the substrate 21 side is not directly involved in sliding as a valve, it may have a dilution ratio of more than 20%, and the dilution ratio has a gradient in the range of more than 0 and not more than 95%.
[0033] Here, the buildup portion 22 or the covering portion 23 is composed of two or more buildup layers, and it is desirable that the dilution ratio of the buildup portion 22 or the covering portion 23 composed of the second or more layers excluding the buildup portion closest to the substrate 21 is 20% or less.
[0034] [Preferable chemical composition of the cladding portion 22 or the coating portion 23] In the wear-resistant members 20 and 20A of the present invention, a cladding portion 22 or a coating portion 23 made of a Cr-based alloy containing Cr as a main component is formed on the surface. The Cr-based alloy contains, in mass %, Cr: more than 40.0% and not more than 65.0%; 0% or more and 30.0% or less of Fe; C is between 0.5% and 2.5%. Mn is 0% or more and less than 2.0%; 0.1% or more and 1.25% or less of Ti; and Nb, more than 0% and not more than 20%; The balance is preferably a Cr-based alloy consisting of Ni and unavoidable impurities.
[0035] The Cr-based alloy of the present invention is a low-cost Cr-based alloy that combines high corrosion resistance and wear resistance by forming Nb-based carbides.
[0036] A description will now be given of suitable chemical compositions (each component) of the Cr-based alloy constituting the cladding portion 22 or the covering portion 23. The content of each element is in mass % unless otherwise specified. Note that the Cr-based alloy according to the present invention preferably has a total content of the disclosed components of more than 99 mass %, and the total content of components other than the disclosed components, such as impurities mixed in during the manufacturing process of the alloy, is preferably less than 1 mass %.
[0037] Cr: More than 40% by mass but not more than 65% by mass The Cr component is the maximum content component of the Cr-based alloy valve of the present invention, and has the advantage of being cheaper than Co, making it possible to reduce material costs compared to conventional Co-based alloys. In addition, by making Cr the maximum content component, a passive oxide film is easily formed on the surface of the Cr-based alloy valve, which has the effect of improving corrosion resistance. The Cr content is preferably more than 40% by mass, more preferably 45% by mass or more, and even more preferably 50% by mass or more. By making the Cr content more than 40% by mass, it is possible to reduce costs and to fully exert the effect of improving corrosion resistance. On the other hand, by making the Cr content 65% by mass or less, it is possible to avoid a melting point of the alloy becoming too high, which would deteriorate the manufacturability of the Cr-based alloy valve (increase in manufacturing costs), so the Cr content is preferably 65% by mass or less.
[0038] Ni: 15% by mass or more and 40% by mass or less The Ni component is one of the main components constituting the parent phase (ferrite phase or a mixed phase of ferrite phase and austenite phase) of the Cr-based alloy valve of the present invention, and is a component that contributes to improving the ductility and toughness of the parent phase. The Ni content is preferably lower than the above-mentioned Cr content and higher than the Fe content described below. Specifically, the Ni content is preferably 15 mass% or more, more preferably 20 mass% or more, and even more preferably 25 mass% or more. By making the Ni content 15 mass% or more, the ductility and toughness of the Cr-based alloy valve can be sufficiently ensured. On the other hand, by making the Ni content 40 mass% or less, the wear resistance of the Cr-based alloy valve can be kept high, so the Ni content is preferably 40 mass% or less.
[0039] Fe: More than 0% by mass and 30% by mass or less The Fe component is also one of the main components constituting the parent phase of the Cr-based alloy valve of the present invention, and is a component that contributes to ensuring toughness and hardness. The Fe content is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 17% by mass or less. By making the Fe content 30% by mass or less, it is possible to suppress the generation of the σ phase (intermetallic compound phase based on the FeCr phase), which is a brittle intermetallic compound, and to avoid a significant decrease in the ductility and toughness of the Cr-based alloy valve (so-called σ phase embrittlement). On the other hand, by making the Cr-based alloy valve not completely free of Fe components (Fe content is 0% by mass), the wear resistance of the Cr-based alloy valve can be maintained, so the Fe content in the Cr-based alloy valve is more preferably 10% by mass or more.
[0040] Nb: 5% by mass or more and 16% by mass or less The Nb component combines with the C component to form and precipitate Nb carbide phases (e.g., NbC phase), which is an important component that contributes to improving the hardening and wear resistance of Cr-based alloy valves. In addition, the Nb component dissolved in the matrix also has the effect of contributing to improving toughness. The Nb content is preferably 5% by mass or more, and more preferably 6% by mass or more. By making the Nb content 5% by mass or more, the hardening and wear resistance of the Cr-based alloy valve is improved. On the other hand, the Nb content is preferably 16% by mass or less, and more preferably 12% by mass or less. By making the Nb content 16% by mass or less, the ductility and toughness of the Cr-based alloy valve is made sufficient. Moreover, the mass ratio C / Nb of the Nb content to the C content described later is preferably 0.11 or more and 0.16 or less, more preferably 0.12 or more and 0.14 or less. By making the mass ratio C / Nb 0.11 or more, it is possible to avoid an insufficient amount of Nb carbide phase being generated, and to avoid an insufficient effect of improving the hardening and wear resistance of the Cr-based alloy valve. By making the mass ratio C / Nb 0.16 or less, the excess C component is prevented from forming a Cr carbide phase (for example, Cr7C3 phase, Cr 23 This prevents the formation and precipitation of the C6 phase, thereby ensuring improved corrosion resistance of Cr-based alloy valves.
[0041] C: 0.6% by mass or more and 2.5% by mass or less The C component combines with the above-mentioned Nb component to generate and precipitate the Nb carbide phase, which is an important component that contributes to the hardening and wear resistance improvement of Cr-based alloy valves. In addition, the C component also has the effect of contributing to the hardening of Cr-based alloy valves even when it is dissolved in the matrix. The C content is preferably 0.6 mass% or more, and more preferably 0.7 mass% or more. By making the C content 0.6 mass% or more, the hardening and wear resistance of the Cr-based alloy valve is improved. On the other hand, the C content is preferably 2.5 mass% or less, more preferably 2 mass% or less, and even more preferably 1.5 mass% or less. By making the C content 2.5 mass% or less, the Cr carbide phase is generated and precipitated in excess, and the corrosion resistance of the Cr-based alloy valve can be ensured. As described above, the mass ratio C / Nb of the C content to the Nb content is preferably 0.11 or more and 0.16 or less, and more preferably 0.12 or more and 0.14 or less.
[0042] Ti: 0.1% by mass or more and 0.9% by mass or less The Ti component combines with oxygen inside the Cr-based alloy valve to form fine Ti oxide particles, and is a component that plays a role in capturing and stabilizing excess oxygen that does not contribute to positive effects (so-called deoxidization role). In addition, the dispersed Ti oxide particles function as starting points (seeds) for the generation of Nb carbide phase, and have the effect of contributing to the fine dispersion precipitation of Nb carbide phase. Note that the present invention does not deny the possibility that a part of the Ti component may form carbides (for example, TiC or (Nb, Ti)C). The Ti content is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more. By making the Ti content 0.1% by mass or more, it is possible to avoid an insufficient amount of Ti oxide particles generated, and to avoid insufficient fine dispersion precipitation of the Nb carbide phase (large clumpy Nb carbide phase particles are likely to precipitate), and as a result, the hardening and wear resistance of the Cr-based alloy valve is sufficiently improved. On the other hand, the Ti content is preferably 0.9% by mass or less, more preferably 0.7% by mass or less, and even more preferably 0.5% by mass or less. By making the Ti content 0.9% by mass or less, it is possible to suppress the Ti oxide particles from easily becoming coarse, and to suppress the Ti oxide particles from easily being unevenly distributed on the solidification surface of the Cr-based alloy valve together with the Nb carbide phase, and it is possible to reliably improve the corrosion resistance and wear resistance of the Cr-based alloy valve. Moreover, the mass ratio Ti / Nb of the Ti content to the above-mentioned Nb content is preferably 0.0062 or more and 0.063 or less, more preferably 0.01 or more and 0.05 or less. By making the mass ratio Ti / Nb 0.0062 or more, it is possible to suppress the tendency of the massive Nb carbide phase particles to become coarse. By making the mass ratio Ti / Nb 0.063 or less, it is possible to suppress the tendency of the Ti oxide particles to become coarse, and to suppress the tendency of the Ti oxide particles to be unevenly distributed on the solidification surface of the Cr-based alloy valve together with the Nb carbide phase.
[0043] Mn: 2% by mass or less Mn is an optional component of Cr-based alloy valves, and combines with sulfur and oxygen to form fine particles of the compound, and plays a role in capturing and stabilizing excess sulfur and oxygen that do not contribute to positive effects (so-called desulfurization and deoxidization role). By capturing and stabilizing sulfur and oxygen, Mn contributes to improving the corrosion resistance, ductility, and toughness of Cr-based alloy valves. Although Mn is not an essential component (its content may be 0 mass%), in order to ensure the effect of Mn inclusion, the Mn content is preferably 0.05 mass% or more. On the other hand, the Mn content is preferably 2 mass% or less, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less. By keeping the Mn content at 2 mass% or less, it is possible to avoid the formation of coarse particles of sulfides (e.g. MnS), which are a factor in reducing the corrosion resistance, ductility, and toughness of Cr-based alloy valves.
[0044] Impurities: Total of 1% by mass or less Representative impurities in the Cr-based alloy valve of the present invention include N, O, P, S, and Ta. These impurities will be briefly explained below. Co is included at a level that is an unavoidable impurity, and is not intentionally added.
[0045] N: 0.04% by mass or less The N component is an impurity component that reduces the mechanical properties (e.g., ductility, toughness) of the Cr-based alloy valve when it combines with the constituents of the Cr-based alloy material to form coarse particles of a nitride phase (e.g., Cr nitride phase). On the other hand, by controlling the N content to 0.04 mass% or less, it becomes possible to dissolve N in the matrix or form fine particles of the nitride phase, which also has the effect of improving the mechanical properties (e.g., hardness).
[0046] O: 0.02% by mass or less The O component is an impurity component that reduces the mechanical properties (e.g., ductility, toughness) of the Cr-based alloy valve when it combines with the constituents of the Cr-based alloy material to form coarse particles of an oxide phase (e.g., Fe oxide). On the other hand, by controlling the O content to 0.02 mass% or less, it becomes possible to form fine particles of the oxide phase, which also has the effect of improving the mechanical properties (e.g., hardness).
[0047] P: 0.04% by mass or less P is an impurity that easily segregates at the grain boundaries of Cr-based alloy valves and reduces the mechanical properties (e.g., ductility and toughness) and corrosion resistance of the grain boundaries. By controlling the P content to 0.04 mass% or less, these negative effects can be suppressed.
[0048] S: 0.005% by mass or less The S component is an impurity component that easily combines with the constituents of Cr-based alloy materials to form sulfides (e.g., Fe sulfides) with relatively low melting points, and reduces the mechanical properties and corrosion resistance of Cr-based alloy valves. By controlling the S content to 0.005 mass% or less, these negative effects can be suppressed.
[0049] Ta: 0.2% by mass or less Ta is one of the components contained in niobium ore (e.g., pyrochlore) and is an impurity component that is easily mixed into Nb raw materials. If the Ta content is 0.2 mass% or less, there is no particular adverse effect. In other words, Ta is not a component that is intentionally contained, but it is a component that is allowed to be contained at 0.2 mass% or less.
[0050] Additional optional ingredients As described above, the Cr-based alloy valve of the present invention may further contain one or more of Cu, Si, Sn, and Al as additional optional components. Next, these additional optional components will be briefly described.
[0051] Cu: 0.1% by mass or more and 5% by mass or less The Cu component is one of the optional additional components in Cr-based alloy valves, and is a component that contributes to improving corrosion resistance. When Cu is contained, its content is preferably 0.1 mass% or more and 5 mass% or less. By making the Cu content 0.1 mass% or more, the action and effect based on Cu can be made clear. On the other hand, by making the Cu content 5 mass% or less, it is possible to avoid Cu precipitates being easily generated, and to avoid them becoming a factor in reducing the ductility and toughness of Cr-based alloy valves.
[0052] Si: 0.1% by mass or more and 1% by mass or less The Si component is also one of the optional additional components in Cr-based alloy valves, and plays a role in deoxidization. When Si is contained, its content is preferably 0.1 mass% or more and 1 mass% or less. By making the Si content 0.1 mass% or more, the action and effect based on Si can be clarified. On the other hand, by making the Si content 1 mass% or less, the formation of coarse particles of oxides (e.g., SiO2) can be suppressed, and it is possible to avoid the reduction in ductility and toughness of Cr-based alloy valves.
[0053] Sn: 0.02 mass% or more and 0.3 mass% or less The Sn component is also one of the optional additional components in Cr-based alloy valves, and plays a role in strengthening the passive film on the surface of the coating layer, and contributes to improving corrosion resistance (e.g., resistance to chloride ions and acidic corrosive environments). When Sn is contained, its content is preferably 0.02 mass% or more and 0.3 mass% or less. By making the Sn content 0.02 mass% or more, the action and effect based on Sn can be clarified. On the other hand, by making the Sn content 0.3 mass% or less, the occurrence of grain boundary segregation of the Sn component can be suppressed, and it can be avoided that it becomes a factor of reducing the ductility and toughness of the Cr-based alloy valve.
[0054] Al: 0.005 mass% or more and 0.05 mass% or less The Al component is also one of the optional additional components in Cr-based alloy valves, and is a component that contributes to improving the deoxidizing effect when combined with Mn and Si. When Al is contained, its content is preferably 0.005 mass% or more and 0.05 mass% or less. By making the Al content 0.005 mass% or more, the action and effect of Al can be clarified. On the other hand, by making the Al content 0.05 mass% or less, it is possible to suppress the formation of coarse particles of oxides and nitrides (e.g., Al2O3 and AlN), and to avoid them becoming a factor in reducing the ductility and toughness of Cr-based alloy valves.
[0055] The alloy described above is preferably formed into alloy powder 10 and overlay welded. The molten alloy of the present invention may be powdered by gas atomization, in which the alloy is introduced into a high-speed inert gas stream and pulverized, and then applied by a PTA (Plasma transfer arc) overlay welding device. In a PTA overlay welding device, the powder is usually transported by moving a pipe to the application part at the tip of the welding torch, so the powder needs to move smoothly. In contrast, the powder obtained by gas atomization is spherical and has good fluidity, which is preferable. In addition, the powdered alloy of the present invention may be sintered into a rod-shaped powder metallurgy compact by powder metallurgy and used as a welding rod.
[0056] [Examples of how to use the wear-resistant members 20 and 20A] The wear-resistant members 20, 20A manufactured as described above can achieve both corrosion resistance and wear resistance. As a result, the wear-resistant members 20, 20A of the present invention can be suitably used as various members used in severe corrosive and wear environments. Examples of applicable members include globe valves, gate valves, etc. in BWR (Boiling Water Reactor) plants, and globe valves, gate valves, etc. in PWR (Pressurized water reactor) plants. Among the above-mentioned members, application to gate valves is particularly preferred.
[0057] 2 and 3 are schematic diagrams of a gate valve 30, which is an example of the wear-resistant member of the present invention. In the gate valve 30, a coating layer 35 made of a Cr-based alloy is formed by overlaying on the opposing contact portions of a valve body 32 and a valve seat portion 31.
[0058] 4 and 5 are schematic diagrams of a globe valve 40, which is another example of the wear-resistant member of the present invention. In the globe valve 40, a coating layer 45 made of a Cr-based alloy is formed by overlaying on the opposing contact portions of a valve body 42 and a valve seat 41.
[0059] 6 and 7 are schematic diagrams of a check valve 50, which is yet another example of the wear-resistant member of the present invention. In the check valve 50, a coating layer 55 made of a Cr-based alloy is formed by overlaying on the opposing contact portions of a valve body 52 and a valve seat portion 51.
[0060] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0061] [Experiment 1] (Preparation of Test Specimens for Examples 1 to 3) For the build-up welding, gas atomized powder having the alloy composition shown in Table 1 (a table showing the alloy composition of the gas atomized powder used in the PTA build-up welding) was prepared.
[0062] [Table 1]
[0063] A MagicWave 4000 MV manufactured by Fronius was used for PTA overlay welding. The PTA welding nozzle was held by a robot, and the powder supply rate was controlled by the feeder rotation speed of the powder hopper. The base material was carbon steel SGV410, which is used for valve seats, and overlay welding was performed under constant current conditions with the current value set to a constant value. At this time, the heat input per weight of the powder was controlled in the range of 10 to 30 kJ / g, and three specimens, test specimens 1 to 3, were produced.
[0064] Figure 8 is a photograph of the appearance of the prepared test specimen 3. The test specimen consists of a base material and an overlay welded part at the center of the base material, and the overlay weld was applied in multiple layers so that the overlay overlapped each other.
[0065] (Test specimen characteristic evaluation method) (1) Dilution ratio measurement The dilution ratio was measured using a scanning electron microscope-energy dispersive X-ray analyzer SEM-EDX (S-4300SE, manufactured by Hitachi High-Technologies Corporation). In overlay welding, the base material melts into the overlay and is diluted. The dilution ratio in the present invention was calculated by calculating the increase in iron, the main component of the base material, from the EDX (Energy dispersive X-ray spectroscopy) analysis value, and calculating the mixing rate of the base material in the overlay from the component ratio of the overlay material and the base material, and this was taken as the dilution ratio. At this time, the iron content of the base material was calculated as 100%.
[0066] 9 is a photograph of the cross section of test piece 3 of the present invention. This build-up cross section was analyzed by EDX at 1 mm intervals from the surface in the depth direction.
[0067] Figures 10 to 12 show the analysis results for specimens 1 to 3, respectively. For all specimens, a general tendency can be seen in which the dilution ratio is low at a distance of 0 mm from the surface, i.e., near the build-up surface, and increases toward the base material. Specimens 1 to 3 have different dilution ratios because they have different build-up conditions.
[0068] (2) Hardness evaluation When opening and closing a valve, a large load is applied to the contact surface between the valve body and the valve seat as they slide. For this reason, it is preferable for the sliding surface to have high hardness characteristics. In the valve overlay portion, a Vickers hardness of 400HV or more is preferable, 500HV or more is preferable, and 600HV or more is even more preferable.
[0069] Therefore, a Vickers hardness test was carried out to investigate the relationship between the dilution ratio and hardness. The test was carried out at room temperature according to the Vickers hardness test of JIS Z 2244. The test force was 1 kgf and held for 10 seconds. Figure 7 shows a photograph of the cross section of the specimen 3 of the present invention. The cross section of the cladding material was mirror-polished, and the hardness was measured at intervals of 1 mm from the surface in the depth direction. Figures 13 to 15 show the analysis results of specimens 1 to 3, respectively. As shown in these Figures 13 to 15, it was found that the outermost surface was the hardest, and that the hardness was high near the surface. It was also confirmed that the hardness decreased as it approached the substrate 21 side.
[0070] To compare the relationship between the dilution ratio and hardness, Figures 16 to 18 show the relationship between the dilution ratio and hardness for specimens 1 to 3. As shown in Figures 16 to 18, it was found that the lower the dilution ratio, the greater the hardness, and the harder the dilution ratio increased, the harder the hardness decreased.
[0071] In particular, good hardness characteristics of Vickers hardness of 400HV or more were obtained with a dilution ratio of 20% or less. High hardness characteristics of Vickers hardness of 500HV or more were obtained with a dilution ratio of 13% or less, and 600HV or more were obtained with a dilution ratio of 6% or less. From the above results, it is recommended that the dilution ratio of Cr-based alloy valves be 20% or less, with 13% or less being preferable, and 6% or less being even more preferable. On the other hand, since the hardness of the buildup surface that actually slides is important for the sliding characteristics of the valve, the dilution rate other than the surface layer of the buildup may be more than 20%, and from the results of Figures 10 to 18, it can be seen that the dilution rate of the buildup portion 22 or the covering portion 23 is determined by the mixing rate of base material 21 in the buildup portion 22 or the covering portion 23, which is determined from the component ratio of the buildup portion 22 or the covering portion 23 to the base material 21 when calculating the increase in the main component of the base material 21 in the buildup portion 22 or the covering portion 23 relative to the alloy powder 10 before the formation of the buildup portion 22 or the covering portion 23, and must be 95% or less from the base material 21 side to the surface of the buildup portion 22 or the covering portion 23, and must have a gradient.
[0072] [Experiment 2] (Preparation of Test Specimens for Examples 4 to 7) As in Experiment 1, PTA overlay welding was performed using gas atomized powder having the alloy composition in Table 1. The substrate was carbon steel SGV410, and overlay welding was performed under constant current conditions with a constant current value. At this time, the heat input per weight of the powder was controlled in the range of 10 to 30 kJ / g, and four specimens, specimens 4 to 7, were prepared. Specimens 4 to 7 were single-layer overlay welding. After overlay welding, specimens with a length of 20 mm, width of 10 mm, and thickness of 2 mm were processed for the corrosion test described later.
[0073] (1) Dilution ratio measurement As in Experiment 1, the dilution ratio was measured using a scanning electron microscope-energy dispersive X-ray analyzer SEM-EDX (Hitachi High-Technologies Corporation, S-4300SE). The dilution ratio in Experiment 2 was determined by EDX analysis of four points on the surface of the corrosion test specimens machined from specimens 4 to 7, calculating the increase in iron, the main component of the base material, from the average value of the four points, and calculating the mixing rate of the base material in the overlay from the component ratio of the overlay material and the base material, which was taken as the dilution ratio. At this time, the iron content of the base material was calculated as 100%.
[0074] As a result, the dilution rates of specimens 4 to 7 were 6.8%, 16.7%, 28.5%, and 40.2%, respectively.
[0075] (3) Corrosion test To evaluate corrosion resistance, a high-temperature, high-pressure underwater corrosion test was carried out. An autoclave manufactured by Toshin Kogyo Co., Ltd. was used for the high-temperature, high-pressure underwater corrosion test. The test specimens used had overlay sections processed to a length of 20 mm, width of 10 mm, and thickness of 2 mm. The test conditions were 288°C and a pressure of 8.3 MPa, and the immersion test was carried out for 1500 hours.
[0076] Figure 19 is a photograph of the appearance after the corrosion test. As shown in this figure, specimens 4 and 5 retained a metallic luster even after the corrosion test, demonstrating good corrosion resistance. On the other hand, corrosion products formed on specimens 6 and 7, covering the surface of the specimens. Specimens 1 and 2 had a dilution ratio of 16.7% or less, while specimens 6 and 7 had a dilution ratio of 28.5% or more. Therefore, it is believed that good corrosion resistance can be obtained by keeping the dilution ratio at 16.7% or less.
[0077] [Dilution rate of the build-up area suitable for valves] It was confirmed from Experiments 1 and 2 that the lower the dilution ratio, the better the hardness and corrosion resistance. In order to summarize the relationship between the dilution ratio and properties, the relationship between the dilution ratio and hardness and corrosion resistance is shown in Table 2.
[0078] [Table 2]
[0079] Hardness was rated as excellent for 600HV or more, good for 500HV or more but less than 600HV, fair for 400HV or more but less than 500HV, and poor for dilution rates where it was not possible to confirm that the dilution was less than 400HV or 400HV or more. Corrosion resistance was rated as good if it had a metallic luster after the corrosion test, and fair if it was covered with corrosion products.
[0080] If it is desired to give the Cr-based alloy valve a particularly high hardness, the dilution ratio should be 20% or less, preferably 13% or less, and more preferably 6% or less. Also, if the Cr-based alloy valve is to be used in a corrosive environment, the dilution ratio should be 16% or less.
[0081] On the other hand, since dilution by the base material of the PTA build-up welding is unavoidable, a large dilution rate does not pose a problem except for the outermost surface of the valve, and may exceed 40%.
[0082] Next, the effects of this embodiment will be described.
[0083] In the wear-resistant member 20 including the substrate 21 of the present embodiment and the overlay portion 22 made of a Cr-based alloy material formed on the surface side of the substrate 21, or in the wear-resistant member 20A including the substrate 21 and the coating portion 23 made of a Cr-based alloy material formed on the surface side of the substrate 21, the overlay portion 22 or the coating portion 23 has a dilution rate determined by the mixing rate of the substrate 21 in the overlay portion 22 or the coating portion 23, which is determined from the component ratio of the substrate 21 to the overlay portion 22 or the coating portion 23 when the increase in the main component of the substrate 21 in the overlay portion 22 or the coating portion 23 relative to the alloy powder 10 before the formation of the overlay portion 22 or the coating portion 23 is calculated, and the dilution rate has a gradient in the range of 95% or less from the substrate 21 side to the surface of the overlay portion 22 or the coating portion 23, and the outermost surface of the overlay portion 22 or the coating portion 23 has a dilution rate of 20% or less.
[0084] Therefore, the wear-resistant members 20, 20A have excellent corrosion resistance and hardness, and therefore Co elution is reduced compared to the conventional case, and it is possible to achieve a longer life and a shorter maintenance time, and to reduce radiation exposure of workers. In addition, the use of a Cr-based alloy makes it possible to provide a lower cost than conventional materials.
[0085] In addition, the buildup portion 22 or the covering portion 23 is composed of two or more layers of buildup portions, and the dilution ratio of the buildup portion 22 or the covering portion 23, excluding the buildup portion closest to the substrate 21, is 20% or less, so that a layer with high hardness and corrosion resistance can be reliably formed on the outermost surface side.
[0086] Furthermore, since the dilution ratio of the outermost surface is 16% or less, the cladding portion 22 or the covering portion 23 can have extremely excellent corrosion resistance.
[0087] Furthermore, since the buildup portion 22 or the covering portion 23 has an area having a dilution rate of 16% or less that is 2 mm or more from the outermost surface, even if wear or the like occurs due to use of the wear-resistant member 20, 20A, a layer with sufficient corrosion resistance and high hardness can be maintained on the outermost surface side for a long period of time, thereby achieving a longer service life.
[0088] <Other> The present invention is not limited to the above-mentioned embodiment, and various modifications and applications are possible. The above-mentioned embodiment has been described in detail to explain the present invention in an easily understandable manner, and the present invention is not necessarily limited to having all of the described configurations. [Explanation of symbols]
[0089] 10...Alloy powder (material) 20, 20A...Wear-resistant material 21...Base material 22…Build-up part (coating layer) 23...Covering portion (covering layer) 30...Shuttle valve 31, 41, 51...Valve seat 32, 42, 52...Valve body 35,45,55…covering layer 40...Globe valve 50...Check valve
Claims
1. A substrate made of carbon steel; A wear-resistant member comprising: a coating layer made of a Cr-based alloy material formed on a surface side of the substrate, the coating layer has a dilution rate determined by a mixing rate of the base material in the coating layer, which is determined from a component ratio of the coating layer to the base material when an increase in a main component of the base material in the coating layer relative to a material before the coating layer is formed, and the dilution rate has a gradient in a range of 95% or less from the base material side to the surface of the coating layer; The outermost surface of the coating layer has a dilution ratio of 20% or less. Wear-resistant material.
2. The wear-resistant member according to claim 1, The coating layer is composed of two or more cladding portions, The dilution ratio of the coating layer excluding the build-up portion closest to the substrate is 20% or less. Wear-resistant material.
3. The wear-resistant member according to claim 1, The dilution ratio of the outermost surface is 16% or less. Wear-resistant material.
4. The wear-resistant member according to claim 3, The coating layer has a region with a dilution rate of 16% or less that is 2 mm or more from the outermost surface. Wear-resistant material.
5. The wear resistant member according to any one of claims 1 to 4, The wear-resistant member is a sliding member or a valve member. Wear-resistant material.
6. A substrate made of carbon steel; A method for manufacturing a wear-resistant member comprising: The coating layer is a dilution rate determined by a mixing rate of the base material in the coating layer, which is determined from a component ratio of the coating layer to the base material when an increase in a main component of the base material in the coating layer relative to a material before the coating layer is formed, has a gradient in a range of 95% or less from the base material side to the surface of the coating layer, The dilution ratio of the outermost surface of the coating layer is 20% or less. Form it so that A method for manufacturing a wear-resistant member.
Citation Information
Patent Citations
High toughness chromium based alloy for hard facing, its powder and engine valve for automobile with the alloy built-up
JP1993271841A